Analysis of Sales Forecasting to Determine the Feasibility of Production Capacity in Ready-to-Drink Industrial Companies with a Rough Cut Capacity Planning Approach - Nadya Evana; Tanggor Sihombing (Publikasi Indonesia, 2025)
This study analyzes the impact of inflation, public holidays, the US dollar exchange rate, and marketing costs on sales at PT XYZ, a packaged tea company that shifted from contract manufacturing to its own brand in 2021. Regression results show that public holidays and marketing costs significantly influence sales, where holidays create seasonal spikes in demand and marketing activities expand market reach. Despite increased sales, production capacity planning was inadequate, forcing reliance on overtime. Using Rough-Cut Capacity Planning (RCCP), this research evaluates capacity shortages and compares expansion strategies. Standard time measurements were applied to each production process, while demand forecasting used five methods, with Multiplicative Decomposition chosen for its lowest MAPE (3.424%). Forecasts from 2025–2027 indicate demand exceeding capacity in work centers such as filling, quality check, cooling, box arrangement, cup-to-box insertion, and taping. To address this, two strategies were compared: overtime and additional labor. Cost analysis revealed that adding labor is the more economical and sustainable option, with projected costs of IDR 23.1 billion (2025), IDR 34.8 billion (2026), and IDR 39.3 billion (2027), while generating attractive ROIs of 21.47%, 23.83%, and 23.78%. These findings highlight the importance of aligning production capacity with demand growth to ensure competitiveness and efficiency in the tea industry.